Hubungan antara status kesehatan gigi dengan kualitas hidup pada manula di Kecamatan Malili , Luwu Timur (The corelation between dental health status and the quality of life in the elderly in District Malili, Luwu Timur) - Ayub Irmadani Anwar (DiscoverSys Inc., 2014)
Negative impact of poor oral health on quality of life in the elderly is an important public health problem. Around theworld, poor oral health in the elderly seemed to edentulous, dental caries and periodontal disease. It was reported astrong correlation between the number of teeth lost by a score of OHIP-14. This study aimed to determine the relationshipof oral health and quality of life of the elderly in District of Malili, East Luwu. Pathfinder pilot survey-based studyconducted in 15 villages in that district on 10-12 November 2011. The subjects were elderly people who come to thevillage hall, which is guided by a questionnaire interviewed and met the inclusion criteria. The results showed that theelderly average index of DMF-T at 11.11, which indicated that the oral health status was significantly positivelycorrelated with quality of life (OHIP-14), with a correlation value of 0.170. It was concluded that the higher the valueof DMF-T, the more affect the quality of life of the elderly.